KARAKTER PENUNTUT ILMU DALAM PERSPEKTIF ISLAM - Bukhari (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2020)
Character for science prosecutors in Islamic perspective is a principle that needs to be considered by knowledge pursuers. In the view of Islam it can be illustrated that there are four ethics namely the application of good intentions before occupying itself as someone who seeks knowledge. Choosing the right teacher for him, one of the teachers is able to do the commands of Allah in accordance with His Shari'a and is able to stay away from it. Every work carried out by someone will begin with prayer and earnest effort, because the key to success is based on the belief and trust in someone. This condition must be occupied by someone and character formation will occur for the prosecutors of Islamic religious knowledge.